2011
DOI: 10.1021/nn2029814
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical Lithiation/Delithiation Observation of Individual Amorphous Si Nanorods

Abstract: In situ electrochemical lithiation and delithiation processes inside a nanobattery consisting of an individual amorphous Si nanorod and ionic liquid were explored. Direct formation of the crystalline Li(22)Si(5) phase due to the intercalation of Li ions was observed. In addition, the role of the electrolyte-nanorod interface was examined. It was observed that the lithiation of Si nanorods is dominated by surface diffusion. Upon the delithiation process, partial decomposition of Li(22)Si(5) particles was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
105
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 32 publications
5
105
1
1
Order By: Relevance
“…It shows high reversibility and stable capacity with prolonged cycling, but the reversible capacity has reached its theoretical limit (~372 mAh g ) [5][6][7], and tin (994 mAh g -1 ) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It shows high reversibility and stable capacity with prolonged cycling, but the reversible capacity has reached its theoretical limit (~372 mAh g ) [5][6][7], and tin (994 mAh g -1 ) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…One problem with this strategy is that it requires the electrode to be cycled to low voltages 20,21 to access the full graphite capacity. At these low voltages, the amorphous Li-silicides (a-Li x Si) formed on lithiation are converted to crystalline phases such as crystalline Li 3.75 Si (c-Li 3.75 Si) 5,12,[22][23][24][25][26][27] , a process that is associated with a large overpotential on delithiation. This approach differs from other practical strategies to improve capacity retention that limit the Si cycling regimes to B1,200-1,500 mAh g À 1 , cycling at higher potentials between different a-Li x Si compositions 3,28 .…”
mentioning
confidence: 99%
“…A range of in situ and ex situ mechanistic studies have recently been reported to investigate the Li-Si system, including in situ nuclear magnetic resonance (NMR) [29][30][31] , in situ X-ray diffraction (XRD) 23,24,27 , in situ transmission electron microscopy (TEM) studies 5,12,22,26,[32][33][34][35][36] and ex situ pair distribution function analysis 30 . These studies show that crystalline Si (c-Si) is converted into a-Li x Si phases during the first lithiation, which transform into a metastable crystalline phase c-Li 3.75 Si at low voltages (o70 mV versus Li) 5,12,[22][23][24][25][26][27] , and possibly over-lithiated phases such as c-Li 3.75 þ d Si 24,29 or Li 4.4 Si/Li 4.2 Si 2, 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Meanwhile, the Coulomb efficiency of the first cycle is of critical importance to most anode materials and determines the cycling behavior afterwards. 18,19 Therefore, it is crucial to uncover what exactly happens in the first lithiation.…”
Section: Introductionmentioning
confidence: 99%